Fundamentals Of Entrepreneurship (ENT300) Business Plan : Saralicious / Siti Nurmaisarah Mohd Hairuddin - Mohd Hairuddin, Siti Nurmaisarah (2020)
Saralicious is a product with high quality and premium chocolate chip cookies. The chocolate chip that I used is from a well-known brand such as beryl’s gourmet bittersweet chocolate chips and also from anchor. It means that I will always make sure that the costumer will appreciate every bite. Plus, I also served a few topping such as dark chocolate, white chocolate and also milk chocolate syrup.